Community Participation and Teacher Accountability : Improving Learning Outcomes in Remote Areas of Indonesia - World Bank (World Bank, Washington, DC, 2020)
The Government of Indonesia has introduced many reforms to improve the quality of education but learning outcomes have continued to lag. Improving the quality of education has been especially challenging in rural and remote areas. Starting in 2016, the World Bank supported the Government of Indonesia’s efforts to promote social accountability to improve teacher performance in remote areas through KIAT Guru. This report provides qualitative insights on how an innovative social accountability model resulted in significant improvements in learning outcomes. The study finds social accountability is more effective when it is linked with a strong and objective enforcement mechanism. KIAT Guru combined a social accountability mechanism (SAM) with a pay-for-performance mechanism (PPM) to improve teacher presence, teacher service performance, and student learning outcomes in remote schools. This report focuses on the results of the qualitative study of the nine case study schools. The nine schools were in three of the five pilot districts: Ketapang, Landak, and Manggarai Barat. The qualitative data collected through the case studies of the nine schools complements the quantitative measurements of the impact of KIAT Guru. The data collected by the qualitative researchers indicate that implementation of the KIAT Guru project had a strong and pervasive impact on the nine schools included in the study. The researchers concluded that in all nine locations, the quality of teaching and school-community relations improved over the course of the project. The researchers concluded that the positive outcomes of KIAT Guru outweighed the challenges that surfaced in the communities they studied. The results from the qualitative study of KIAT Guru indicate that social accountability linked to pay based on teacher presence (SAM+Cam) shows the greatest potential for leveraging change in teacher behavior.